PREPARATION OF PHYSICAL EDUCATION AND SPORTS SPECIALISTS FOR THE FORMATION OF STUDENTS’ ECOLOGICAL COMPETENCE THROUGH THE ORGANIZATION OF TOURIST ACTIVITIES (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the topical problem of forming ecological competence in students by specialists in physical education and sports. The paper substantiates the need to integrate environmental education into the process of professional training, given the growing role of environmental awareness in modern society. It is determined that ecological competence is an integrative personal characteristic that combines cognitive, affective, and behavioral components. Scientific works devoted to the formation of ecological competence are analyzed, and it is revealed that tourist activity is an effective means of its development. The expediency of using tourist activity as a pedagogical tool for the formation of students' ecological competence is substantiated. The article identifies the key components of environmental training of future specialists in physical education and sports, including fundamental ecological knowledge, methodological and pedagogical knowledge, practical skills, and value-motivational orientations. Specific directions for the implementation of acquired competencies through the integration of tourist activities into the educational process are proposed, such as the design of environmentally oriented routes, the use of tourism to form environmental awareness, and the development of practical skills in environmentally safe behavior. The importance of using an interdisciplinary approach and interactive teaching methods for the effective formation of ecological competence is emphasized. A list of disciplines that form the necessary competencies for future specialists in physical education and sports at the National University of Physical Education and Sports of Ukraine is determined. Prospects for further research are aimed at developing and testing methods for forming the ecological competence of higher education students through tourist activities. It is advisable to study the impact of various types of tourist activities on the formation of individual components of ecological competence, as well as to explore the possibilities of using information and communication technologies to support this process.
Keywords: ecological competence; ecological education; tourist activity; specialists in physical education and sports